Integration of Islamic Boarding School and Madrasah Education from the Perspective of Kiyai Muhammad Syamsul Arifin - Muhsin Muis; Miftahul Huda (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
This research aims to examine the thoughts of KH. Muhammad Syamsul Arifin regarding the integration of Islamic boarding schools (pesantren) and traditional Islamic schools (madrasah). The study employs a qualitative approach, specifically a literature review. Data collection techniques involve documentation, while content analysis is utilized for data analysis. The research findings reveal KH. Muhammad Syamsul Arifin as an individual with unique ideas concerning the integration of pesantren and madrasah. He firmly believes in the significance of this integration as a means to bridge knowledge gaps and meet the demands of current career prospects. According to KH. Muhammad Syamsul Arifin, if pesantren remain disconnected from the evolving educational systems, there's a potential risk of them becoming obsolete in the face of globalizing developments